Young children's concepts of money - Juachon, Marilou R.; Ronquillo, Carolyn Victoria U. (2003)
This study investigated the development of children's concepts of money in 3 aspects: recognition of money, their perceptions on money, and money-math skills. Forty-two children, 3,5, and 7 years old from a middle class community participated in the study. A self-designed tool was administered in the child's dominant language. Percentage distribution tables, corroborated by the primary analytical tools. Results indicate that children's concepts of money become more defined and elaborate with age. Very young children manifest a lack of awareness about buying, the true sources of money and its finitude. With age, children distinguish coins from bills; they become more aware of the necessity of money in trade and the finitude of money. Performance in money tasks is strongly limited by math skills. Early knowledge of numbers is characteristically verbal in nature. Conceptual understanding of currency units emerges later than that of numbers/ Conceptual understanding of currency money-math skills proved more efficient and accurate.
Thesis (M.F.L.C.D)--University of the Philippines, Diliman.
Keywords: Mathematics -- Study and teaching (Primary) -- Philippines -- Quezon City; Money -- Study and teaching (Primary) -- Philippines -- Quezon City; Number concept in children -- Philippines -- Quezon City